PEMBENTUKAN KELOMPOK USAHA BERSAMA DI DESA HAYA KABUPATEN MALUKU TENGAH DALAM UPAYA MENYELESAIKAN PERMASALAHAN PERIKANAN PANCING ULUR TUNA - Haruna Haruna; F. D Silooy; R. H. S Tawari; Agustinus Tupamahu; S. R. Siahainenia; J. B. Paillin; Selfi Sangadji (Jurnal Abdi Insani, 2023)
Poverty among fishermen is a complex problem and often occurs in many coastal areas and small islands. Fishermen depend heavily on fish catches for their income, however, they are very vulnerable to seasonal fluctuations, climate change, limited infrastructure, access to capital, social security and price competition. The factors faced by fishermen cause unstable economic conditions and make them vulnerable to poverty. This condition is also experienced by tuna handline fishermen in Haya Village, Central Maluku Regency. Community Service Activities (PKM) aim to identify problems with small-scale tuna handline fisheries and assist in the institutional formation of a Joint Business Group (KUB) for tuna handline fisheries in Haya Village. Implementation of activities begins with training, Participatory Rural Appraisal (PRA) and assistance in establishing KUB. This activity is in the form of a Forum Group Discussion (FGD) with partners and other stakeholders. Mitra is a small-scale tuna hand-line fisherman who has experience and is of productive age. The results of identifying partner and stakeholder problems through the Focus Group Discussion (FGD) method are decreasing fish resources, weak availability of facilities and infrastructure, low technology, weak institutions, and not yet optimal policy implementation. In this PKM activity, fishing operation management material is presented as material for gaining knowledge, experience and real conditions of fishermen management in handline fishing activities. All participants were very enthusiastic about taking part in this activity by providing feedback and suggestions for developing their fisheries business in the future. The implementation of the formation of Joint Business Groups (KUB) is expected to be able to overcome fishermen's problems, provide motivation, and be innovative and collaborative in groups. PKM activities were carried out well, apart from that, partners had increased capability, cooperation, communication and commitment within the group for fisheries business development.